2018
DOI: 10.1007/s10798-018-9446-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the use of spatial reasoning strategies in geometric problem solving

Abstract: A core aim of contemporary science, technology, engineering, and mathematics (STEM) education is the development of robust problem-solving skills. This can be achieved by fostering both discipline knowledge expertise and general cognitive abilities associated with problem solving. One of the most important cognitive abilities in STEM education is spatial ability however understandings of how students use this ability in practice are currently underdeveloped. Therefore, this study aimed to investigate how level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 52 publications
1
30
2
3
Order By: Relevance
“…Though there is no consensus on precisely which mental abilities are encompassed by this general term, commonly referenced components include spatial orientation, spatial location memory, targeting, spatial visualization, disembedding and spatial perception (for further detail on these concepts, please see [Kim00]). Individuals with high spatial ability tend to excel in scientific and engineering fields [WLB09] and exhibit stronger problem‐solving skills for various tasks [WHA*02, CKT16, SDL*18], including solving mathematical [YLM18] and geometric problems [BSC19]. Some commonly used tests for spatial ability include the paper folding test [EDH76] and mental rotation test [VK78].…”
Section: Cognitive Abilitiesmentioning
confidence: 99%
“…Though there is no consensus on precisely which mental abilities are encompassed by this general term, commonly referenced components include spatial orientation, spatial location memory, targeting, spatial visualization, disembedding and spatial perception (for further detail on these concepts, please see [Kim00]). Individuals with high spatial ability tend to excel in scientific and engineering fields [WLB09] and exhibit stronger problem‐solving skills for various tasks [WHA*02, CKT16, SDL*18], including solving mathematical [YLM18] and geometric problems [BSC19]. Some commonly used tests for spatial ability include the paper folding test [EDH76] and mental rotation test [VK78].…”
Section: Cognitive Abilitiesmentioning
confidence: 99%
“…According to Gorgorió (1998), in order to solve a spatial task, it is possible to follow a kind of strategy that is not grounded on visual objects and processes. Participants with lower levels of spatial capacity tend to use models allowing them to avoid spatial reasoning (Buckley, Seery, and Canty, 2019). In the analysis performed on the configurations, all the configurations obtained are visual configurations (Godino et al, 2012) and it has been observed, through their cognitive configurations, how the students have mostly used visual arguments when solving the tasks proposed.…”
Section: High-level: Levels 3 Andmentioning
confidence: 99%
“…From a more interdisciplinary point of view, spatial ability has been shown to correlate with academic performance in multiple areas -including other domains in mathematics, as has been said-and postulated as one of the most important cognitive abilities in STEM education (Lubinski, 2010;Rafi, Anuar, Samad, Hayati, & Mahadzir, 2005;Verdine, Golinkoff, Hirsh-Pasek, & Newcombe, 2014). However, a deeper understanding of how students use this ability in practice is still necessary (Buckley, Seery, & Canty, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial ability or visuo-spatial ability is the capacity to comprehend, reason and remember the spatial relations among objects or space 1 . It is of value for the success in engineering and other technical fields.…”
Section: Introductionmentioning
confidence: 99%